Antibiotic resistance: a mechanistic overview - Woodford, Neil (Henry Stewart Talks, 2009)
Modes of antibiotic action, Modes of resistance, Intrinsic / acquired resistance, Emergence and transfer of resistance, Monitoring spread, Modified targets, Enzymic destruction, ESBLs, Plasmidic multi-resistance, Impermeability / porin loss, Carbapenemases, Efflux pumps